Clinical Manifestations of Recurrent Parotid Pleomorphic Adenoma - Myung-Whan Suh; J Hun Hah; Seong Keun Kwon; Young-Ho Jung; Tack-Kyun Kwon; Kwang Hyun Kim; Myung-Whun Sung (Clinical and Experimental Otorhinolaryngology, 2009)
ObjectivesThis study was undertaken to confirm the clinical characteristics of recurrent pleomorphic adenoma (RPA), and to identify those factors that affect the development of malignant transformation (MT) from RPA.MethodsThe medical records of 270 patients, who were operated upon for parotid PA, were retrospectively reviewed. The pathologic specimens of a selected series of 23 patients were reviewed for histologic subtype and microscopic multi-nodularity.ResultsMean age of initial operation in RPA without MT (RPA-MT) group was significantly lower than that of primary PA group. Mean age of the revision operation in RPA with MT (RPA+MT) group was significantly greater than that of RPA-MT group. Mean interval from operation to recurrence shortened after each revision operation. The risk of MT and additional recurrence increased significantly with recurrence. In RPA-MT group tumor recurrence occurred in 21.4% of patients despite a clear resection margin.ConclusionThe risk factors for MT may be an age of over 45 yr and multiple recurrences. However, younger patients are more at risk of recurrence. A clear resection margin cannot guarantee a cure in RPA, and it seems that parotid pleomorphic adenomas slowly gain malignant characteristics after repeated recurrences.